2013
DOI: 10.1051/0004-6361/201321412
|View full text |Cite
|
Sign up to set email alerts
|

The circumstellar environment and evolutionary state of the supergiant B[e] star Wd1-9

Abstract: Context. Historically, supergiant (sg)B[e] stars have been difficult to include in theoretical schemes for the evolution of massive OB stars. Aims. The location of Wd1-9 within the coeval starburst cluster Westerlund 1 means that it may be placed into a proper evolutionary context and we therefore aim to utilise a comprehensive multiwavelength dataset to determine its physical properties and consequently its relation to other sgB[e] stars and the global population of massive evolved stars within Wd1. Methods. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
57
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 153 publications
8
57
0
Order By: Relevance
“…Recently, the LHA 120-S 35 membership to the cluster SL 482 has been discussed by Bitsakis et al (2017), who were able to determine the members of the star cluster using a robust decontamination technique, providing a probability of more than 92% that LHA 120-S 35 is member of the cluster. The previously reported B[e]SGs associated to open clusters are: LHA 120-S 111, which belongs to the compact cluster NGC 1994 of the LMC (Melgarejo et al 2001;Lortet & Testor 1988) and Wd1-9, which is a member of the massive Galactic stellar cluster Westerlund 1 (Clark et al 2013b;Fenech et al 2017). The small number of B[e]SGs found in stellar clusters is reasonable taking into account that their lifetime in this post-main-sequence phase is relatively short.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Recently, the LHA 120-S 35 membership to the cluster SL 482 has been discussed by Bitsakis et al (2017), who were able to determine the members of the star cluster using a robust decontamination technique, providing a probability of more than 92% that LHA 120-S 35 is member of the cluster. The previously reported B[e]SGs associated to open clusters are: LHA 120-S 111, which belongs to the compact cluster NGC 1994 of the LMC (Melgarejo et al 2001;Lortet & Testor 1988) and Wd1-9, which is a member of the massive Galactic stellar cluster Westerlund 1 (Clark et al 2013b;Fenech et al 2017). The small number of B[e]SGs found in stellar clusters is reasonable taking into account that their lifetime in this post-main-sequence phase is relatively short.…”
Section: Discussionmentioning
confidence: 72%
“…Inspection of the profiles of the He i λ 5876 line, which seems to be the only unblended absorption line in the optical spectrum of LHA 120-S 35 reveals that this line also shows variability in its profile that might originate from stellar pulsations. Alternatively, even though evidence indicative of binarity has not yet been found in LHA 120-S 35, a Roche lobe overflow phase in an interacting binary or a colliding-wind binary system could also be suitable scenarios to analyse the complex circumstellar ring-like (and possibly spiral) structures of LHA 120-S 35, as for example in RY Scuti (Smith et al 2011) or Wd1-9 (Clark et al 2013b). However, emission in key lines attributed to binarity as N iii λλ 4634-42 and He ii λ 4686 is not seen, conversely to what was detected in B[e]SGs known to be binaries like LHA 115-S 18 (Clark et al 2013a) and HD 38489 (Massey et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In particular we highlight the binary supergiant B[e] star Wd1-9, which currently appears to be undergoing the rapid case A evolution we hypothesise for Wd1-5 ( Fig. 10; Clark et al 2013). …”
Section: Evolutionary Pathways For Massive Stars In Wd1mentioning
confidence: 73%
“…The presence of strong He ii emission in NaSt1, however, suggests a significantly hotter ionization source than that of Wd1-9, which does not exhibit He ii emission. Clark et al (2013) interpreted the double-peaked line profiles of Wd1-9 as being the result of quasi-Keplerian rotation in a massive disk or torus. This interpretation has also been invoked to explain the double-peaked line profiles detected in the LBV binary MWC 314 (Lobel et al 2013; also shown in Figure 9).…”
Section: Is Nast1 the Product Of Mass Transfer?mentioning
confidence: 99%